TYPES OF ANTIBIOTICS ACCORDING TO THE SCOPE OF THEIR EFFECT AND THEIR IMPORTANCE IN THE HEALTH CARE SYSTEM (British Journal of Global Ecology and Sustainable Development, 2023)
Antibiotics are one of the most important tools in the fight against bacterial infections in the healthcare system. They revolutionized modern medicine and saved countless lives. In this article, we explore the importance of antibiotics in the healthcare system.